Nature, spirit and second nature: Hegel and McDowell - Schuringa, Christoph (Revista Eletrônica Estudos Hegelianos, 2018)
Both Hegel and McDowell make use of the expression ‘second nature’. Furthermore, each philosopher is concerned to connect talk of ‘second nature’ with a larger issue: that of the relation between nature and spirit. According to McDowell, being ‘reminded’ of the perfectly familiar phenomenon of second nature is to do the work of ‘deconstricting’ the conception of nature that bald naturalists operate with. Hegel, by contrast, works in the opposite direction. For Hegel, the phenomenon of second nature is to be understood in light of a prior characterization of the relation between nature and spirit, according to which spirit is the ‘truth of’ nature. This essay attempts to get into focus the difficulties (beginning from the surface grammar of the expressions ‘nature’, ‘second nature’, and ‘first nature’) that must be sorted out before we can properly understand how each philosopher connects the topic of second nature with the wider issue of how nature and spirit are related, and to provide a sketch of the philosophical issues that must be faced once we have the difficulties clearly in view. The philosophical difficulties faced by Hegel differ from those faced by McDowell, as reflects their difference in approach. Those faced by Hegel concern how precisely to spell out the conception of nature – such that ‘spirit is the truth of nature’ – in which his conception of second nature is embedded; those faced by McDowell concern how his ‘reminder’ about second nature is to be understood in the absence of something analogous to Hegel’s attempts to spell out a conception of nature.